The effects of Provent on moderate to severe obstructive sleep apnoea during continuous positive airway pressure therapy withdrawal: a randomised controlled trial. Issue 9 (30th May 2013) - Rossi, Valentina A; Winter, Barbara; Rahman, Najib M; Yu, Ly-Mee; Fallon, Janet; Clarenbach, Christian F; Bloch, Konrad E; Stradling, John R; Kohler, Malcolm
Abstract : Objectives: The aim of this study was to test the effectiveness of Provent, an expiratory nasal resistance valve, to prevent the recurrence of OSA following CPAP withdrawal. Design: Randomised, partially blinded, parallel, placebo-controlled trial. Setting: Outpatient sleep clinics in the UK (Oxford) and Switzerland (Zurich). Participants: 67 patients with OSA receiving CPAP were randomised to one of three groups for 2 weeks: continuing CPAP, Provent or placebo Provent. Main outcome measures: Primary outcomes included for Provent versus placebo Provent, OSA severity (oxygen desaturation index (ODI), apnoea–hypopnoea index (AHI)) and Epworth Sleepiness Scale (ESS) score. Secondary outcomes for Provent versus placebo Provent included ODI from ambulatory pulse oximetry and blood pressure (BP). For CPAP versus Provent, or CPAP versus placebo Provent, secondary outcomes included ODI/AHI, ESS and BP. Results: 63 patients were included in the per protocol analysis. OSA recurred in the Provent (ODI 35.8, SD 17.4) and placebo Provent (ODI 28.2, SD 18.3) groups, and there was no significant difference in ODI, AHI and ESS between Provent and placebo Provent at 2 weeks (mean difference ODI −1.0, 95% CI −10.0 to +12.0, p=0.85; AHI +3.2, 95% CI −7.7 to +14.1, p=0.52; and ESS −1.4, 95% CI −4.1 to +1.4, p=0.33). ODI from ambulatory pulse-oximetry and BP at 2 weeks were not different in the Provent versus placebo Provent groups. ODI, AHI and BP, but not ESS, were significantly higher in the Provent and placebo Provent groups compared with CPAP. Conclusions: Provent cannot be recommended as an alternative short-term therapy for patients with moderate to severe OSA already on CPAP. TrialRegNo: NCT01332175.